SITUS-SITUS ARKEOLOGI DI DAERAH GEGUNUNG SEBAGAI JEJAK PERMUKIMAN AWAL DI CIREBON - Nanang Saptono; Endang Widyastuti (JURNAL PANALUNGTIK, 2019)
Since a period of Hindu-Buddhist influence,Cirebon region has been an important area, although geographically not as a government center. The existence of the Huludayeuh inscription shows that the area was noticed by the rulers of the Sunda Kingdom. When the Sunda Kingdom suffered a setback and Muslim communities on the coast developed to form political power, the southern region of Cirebon flourished. One of the developing settlements is the Gegunung Village on the edge of Ci Pager. This study shows some archaeological objects in the area. The results of this study are expected to be used as input for policy decisions in the management of ancient relics. In Gegunung Village there are several petilasan as an early sign of the emergence of settlements. Based on oral traditions, the emergence and development of these settlements began with a border guard post.